Аналіз енергоспоживання 3D‐принтеру на технологічному шляху виготовлення виробу за допомогою технології FDM з можливістю подальшої утилізації - Вишневецький, В. В. (НТУ ДП, 2022)
В роботі проведений аналіз енергозатрат 3D‐принтеру Flying Bear Ghost 5 під час експлуатації. Розраховано собівартість виготовлення днища корпусу трансмісії, з можливістю використання розрахунків для інших виробів. Розглянута можливість рециклінгу виробів з ABS пластику.

The analysis of energy consumption of 3D‐printer Flying Bear Ghost 5 during operation is carried out. The cost of manufacturing the bottom of the transmission case is calculated, with the possibility of using calculations for other products. The possibility of recycling ABS plastic products is considered.
3D printer energy consumption analysis on the technological way of manufacturing a product using fdm technology with the possibility of further utilisation
Keywords: собівартість 3D‐друку; аналіз енергоспоживання 3D‐принтеру; рециклінг ABS; cost of 3D‐printing; analysis of energy consumption of 3D‐printer; ABS recy‐cling